Development of anionic-cationic inhibitors for mitigating silicate scales during ASP flooding - Mahat, S.Q.A. (Elsevier B.V., 2017)
Silicate scaling is often induced by alkaline surfactant polymer (ASP) flooding in sandstone reservoirs. The formation of silicate scale is complicated by its dependence on multiple factors including pH, silica concentration, and magnesium concentration, which vary as the flood progresses. These factors affect silicate scaling tendency, and consequently, severity of the problem. Silicate scale is a very serious problem in the oil and gas production system. Therefore, silicate scale inhibitors have been suggested to mitigate problems in oilfields. In this study, some of the dendrimers inhibitors with enhanced functionality used in the water industry were reviewed and assessed for possible application in oilfields scales. It was found that the NH2-terminated dendrimers exhibited excellent inhibitory silica polymerization efficiency compared with the control. It is now certain that effective silica scale inhibition is dependent on the cationic charge on the polymer backbone. However, these dendrimer inhibitors suffered from a serious disadvantage when the silicates that had not been inhibited entrapped the dendrimers. Visual observations showed that these particles appeared as white flocculant precipitates at the bottom of the test vessels. Previously, it had been found that silica scale inhibition could be achieved by using of scale inhibitors in combination with anionic polymer additives. It is believed that an effective silica inhibition should be based on a delicate balance structure of cationic–anionic charges. Therefore, in the present study pteroyl-L-glutamic acid (PGLU) compound is used in synergistic action with cationic dendrimer polymer. PGLU was proven to be an effective scale inhibitor at high temperature in aqueous solution of synthetic produced water. Furthermore, it was found that PGLU assisted the inhibitory action of dendrimers by alleviating formation of insoluble SiO2-PAMAM precipitates to operate more effectively. © 2016 Elsevier B.V.